Um Breve Retrato do Perfil Empreendedor - Brito, Sílvio Manuel; Honrado, Maria Graciete (Journal Of Exact Sciences and Technological Applications, 2021)
In the actual times, we live, every day, the globalization vicissitudes, in a quick and unexpected time. In this direction, we verify that, before the actors change markets, rules and norms, forms of communication, and management instruments, the organizations look for to develop and to hold back the talents in a competitive and global market. Therefore, we try to identify in the literature, watching recent work, instruments, and procedures, which justified eventual essential deemed entrepreneurship competencies, in order to confirm an entrepreneurial profile that can lead a company to the development. For that, we use a monographic methodology. According to what, we could verify that, in the actual reality, it confirms the existence of such profile.